The effect of Sugar Concentration and Incubation Time on the Quality of Purple Sweet Potato Extract Probiotic Drink - Desy Lyan Sari Simanjuntak; Sentosa Ginting; Terip Karo-Karo (Universitas Sumatera Utara, 2013)
This research was conducted to determine the effect of sweet sugar concentration and time of incubation on the quality of purple sweet potato probiotic juice. The research was perfomed in december 2012-January 2013 at the Laboratory of Food Technology, University of Sumatera Utara Medan, using completely randomized design with two factors, i.e, the concentration of glucose (G1): 2%, (G2): 3%, (G4): 4%, (G5): 5% and duration of incubation (I1): 4 hours, (I2): 8 hours, (I3): 12 hours, (I4): 16 hours. Parameters analyzed were total soluble solid (oBrix), pH, protein content (%), total microbial ( CFU / g), viscosity (dp.a), organoleptic values of color, flavor and taste. The results showed that the concentration of sugar gives had highly significant different effects on total soluble solid (oBrix), pH, protein content (%), total microbial (CFU / g), viscosity (cp), organoleptic values of color, falvor and taste and the effect of incubation time differed significant on total soluble solid ( oBrix), pH, protein content (%), total microbial (106 x CFU / g), viscosity (cp), organoleptic values of color, aroma and taste. The concentration of sugar of 2% and incubation time of 12 hours resulted in the taste and more acceptable. . Key words : Purple Sweet Potato Juice, Sugar Concentration, Time of incubation